Soil organic matter fractions, chemical attributes and aggregation under forestry and agricultural systems - Silva, Cristiane Figueira da; Pereira, Marcos Gervasio; Feitosa, Júlio César Fernandes; Fonseca Júnior, Ariovaldo Machado; Gaia-Gomes, João Henrique; Menezes, Carlos Eduardo Gabriel (Comunicata Scientiae, 2018)
The aim of this work was to evaluate the influence of the conversion of forest systems to agricultural systems in the organic matter compartments, aggregation and soil chemical attributes, in the Atlantic Forest. The evaluated systems were: annual crop (ACr); perennial agriculture (PAg); pasture; and secondary forest early (SFES), medium (SFMS), and advanced stage (SFAS). Soil samples were collected at the layer of 0-5 cm depth and quantified the total organic carbon (TOC), C of humic substances, oxidizable C, granulometric fractions of soil organic matter (SOM), soil chemical attributes, soil aggregation and glomalin-related soil protein (GRSP-total and GRSP-easily extractable) in different aggregate classes. It was observed a reduction of the TOC, particulate organic carbon (POC), humic substances and oxidizable C in the PAg and ACr areas comparing to pasture and forest systems. Moreover, the pH values increased whereas P content decreased in comparison with SFAS. As for aggregation, the PAg and the ACr decreased by around 35% and 20% the mean weight diameter of aggregates, respectively, compared to the average values found in the forestry systems, and 34% and 45%, respectively in relation to pasture. In general, GRSP-total were reduced by agriculture. Thus, it appears that the agriculture which has been practiced is altering negatively the soil chemical, physical and biological attributes.